2015
DOI: 10.1086/681251
|View full text |Cite
|
Sign up to set email alerts
|

Origin Matters: Diversity Affects the Performance of Alien Invasive Species but Not of Native Species

Abstract: Online enhancement: appendix. Dryad data: http://dx.doi.org/10.5061/dryad.81nk5.abstract: At local scales, it has often been found that invasibility decreases with increasing resident plant diversity. However, whether resident community diversity similarly resists invasion by alien versus native species is seldom studied. We examined this issue by invading constructed native plant assemblages that varied in species and functional richness with invasive alien or native Asteraceae species. Assemblages were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Still, differences in interactions with the resident community increased biotic resistance to alien species (Knapp & Kühn ; Sun et al . ). Higher biotic resistance for alien species runs contrary to most hypotheses (Buckley & Catford ), yet it is not without precedent (Sun et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Still, differences in interactions with the resident community increased biotic resistance to alien species (Knapp & Kühn ; Sun et al . ). Higher biotic resistance for alien species runs contrary to most hypotheses (Buckley & Catford ), yet it is not without precedent (Sun et al .…”
Section: Discussionmentioning
confidence: 97%
“…Higher biotic resistance for alien species runs contrary to most hypotheses (Buckley & Catford ), yet it is not without precedent (Sun et al . ). Importantly, establishment and the biotic effects on establishment were related to different aspects of the community and environment for native and alien species, suggesting important functional differences between these species groups despite close phylogenetic relationships.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Using multiple native and non‐native Asteraceae species, Sun et al . () demonstrated that invasibility declined with increasing recipient community species richness when the invader was non‐native but not when it was native.…”
Section: A New Framework For the Effects Of Biogeographic Origin On Imentioning
confidence: 99%